2018
DOI: 10.1111/dom.13196
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects on glycaemic control and β‐cell preservation of early intensive treatment in patients with newly diagnosed type 2 diabetes: A multicentre randomized trial

Abstract: The findings indicate that outpatient clinic-based IIT to ensure euglycaemia in newly diagnosed patients with T2DM might be an effective initial therapeutic option for improvements in β-cell function and glycaemic control over the long term, without serious adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…We found a dose‐dependent association between the incidence of remission and BMI reduction regardless of baseline BMI, but this association was stronger with BMI of 27.5‐29.9 and slightly attenuated with BMI ≥30.0. This finding suggested that remission accompanied by weight loss may be achieved in patients with type 2 diabetes who have relatively mild increases in BMI through improvement in systemic inflammation, insulin resistance, β‐cell function 30–32 and fatty liver 33,34 in East Asians. The ORs for remission increased about two‐fold in those with 3.0‐6.9% BMI reductions than in those with changes in BMI <3%, suggesting that a relatively small weight loss may have a positive effect on remission of diabetes in Asians.…”
Section: Discussionmentioning
confidence: 98%
“…We found a dose‐dependent association between the incidence of remission and BMI reduction regardless of baseline BMI, but this association was stronger with BMI of 27.5‐29.9 and slightly attenuated with BMI ≥30.0. This finding suggested that remission accompanied by weight loss may be achieved in patients with type 2 diabetes who have relatively mild increases in BMI through improvement in systemic inflammation, insulin resistance, β‐cell function 30–32 and fatty liver 33,34 in East Asians. The ORs for remission increased about two‐fold in those with 3.0‐6.9% BMI reductions than in those with changes in BMI <3%, suggesting that a relatively small weight loss may have a positive effect on remission of diabetes in Asians.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, people with baseline HbA1c <7.0% have a shorter duration of diabetes than those with HbA1c of 7% to 9.9% (Table S4). Patients with newly diagnosed diabetes mellitus achieved remission with intensive treatment 5,36–41 . Early intensive therapies have had favourable outcomes on recovery and maintenance of β‐cell function 5,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with newly diagnosed diabetes mellitus achieved remission with intensive treatment. 5,[36][37][38][39][40][41] Early intensive therapies have had favourable outcomes on recovery and maintenance of β-cell function. 5,39 Therefore, screening of asymptomatic adults for type 2 diabetes may allow earlier detection, diagnosis and treatment.…”
Section: Person-years Was Approximately Twice As High In East Asian V...mentioning
confidence: 99%
“…In subsequent studies, randomized clinical trials were performed to compare conventional treatment and different insulin treatment methods, and status was evaluated to determine whether remission was reached ( Table 3 , Fig. 2 ) [ 50 - 54 ]. Remission following intensive insulin therapy has been demonstrated to last more than 2 years, and it is believed that the shorter the time interval between diagnosis and intensive insulin therapy is, the greater the likelihood of remission [ 10 ].…”
Section: Strategies For the Remission Of Type 2 Diabetes Mellitusmentioning
confidence: 99%